The application of the Geneva Conventions in the absence of an armed conflict: The case of the Chilean military dictatorship - Fernández Carter, Catalina (2021)
This article examines the decisions of the Chilean Supreme Court, which has invoked and applied the Geneva Conventions to the events that occurred during the Chilean military dictatorship that took place between 1973 and 1990. As will be explained, these norms have allowed the Court to render ineffective the amnesty dictated by the military regime and to disregard the statute of limitations for the crimes of imprisonment, torture, murder and forced disappearance, among others. Notably, however, the Supreme Court has overlooked the requirements for the application of international humanitarian law, and has relied almost exclusively on the declaration of war issued by the Junta de Gobierno in the early days of the dictatorship. This has allowed the Court to provide for an extensive application of international humanitarian law, which ignores its fundamental elements, including the distinction between international and non-international armed conflicts. In this context, this paper questions this reasoning, exposes the risks it entails, and demonstrates the existence of an alternative legal regime -international human rights law- that not only provides greater protection, but also adequately reflects the reality of the events that took place during the dictatorship, and the abuse and state violence to which the Chilean population fell victim, without resistance.